Localized morphea after breast implant for breast cancer: A case report. Issue 6 (December 2018) - Moretti, A; Bianchi, F; Abbate, IV; Gherardi, G; Bonavita, M; Passoni, E; Nazzaro, G; Bramati, A; Dazzani, MC; Piva, S; Paternò, E; Frungillo, N; et al.
Purpose: Early breast cancer follow-up guidelines for patients who underwent surgery suggest a regular and accurate clinical examination of the breast area, for an early identification of cutaneous or subcutaneous breast cancer relapse. Nonetheless, breast skin lesions arising in patients treated with mastectomy for breast cancer can be caused by several diseases. A series of diagnostic hypotheses should be considered, not only focusing on cutaneous metastasis, but also on dermatologic and systemic diseases. Case report: In February 2015, a 37-year-old patient underwent a right subcutaneous mastectomy for stage IIA breast cancer. Five months after beginning adjuvant chemotherapy, she noted hyperpigmentation and thickening of the skin on the right breast. Differential diagnosis included local relapse, skin infection, lymphoma, or primary cutaneous disease, and a skin biopsy was performed. The histopathologic specimen showed full-thickness sclerosis, with features of localized morphea. Therapy with clobetasol was prescribed, with progressive resolution of the thickness. The collaboration between many professionals in a multidisciplinary team (oncologist, dermatologist, plastic surgeon, and pathologist) was crucial to achieving the diagnosis. Conclusion: In the literature, some articles describe correlation between connective tissue diseases and silicone breast implants, but the pathogenetic mechanisms are unknown. We report a rare case of breast morphea after positioning a silicone implant in a patient who had undergone mastectomy. This clinical report represents an interesting model of multidisciplinary management of a patient with breast cancer who developed an uncommon dermatologic disease. Further studies are needed to clarify the association between silicone implants and breast morphea.